Sensitivity to rewards and punishments in karate athletes: an examination of the temperamental characteristics and profile of karate competitors according to the revised reinforcement sensitivity theory - Kusnierz, C.; Rogowska, A. M.; Görner, K.; Wosinekm, P. (BMC Sports Science, Medicine and Rehabilitation, 2024)
Background The revised Reinforcement Sensitivity Theory (rRST) assumes the existence of three systems controlling motivation and behavior: the behavioral activation system (BAS), the behavioral inhibition system (BIS), and the fight-flight-freeze system (FFFS). This study aims to examine for the first time the features of BAS, BIS, and FFFS among karate players in comparison with athletes representing other sports disciplines (physical education students) and physically inactive people. The specific configuration of temperament traits and profiles characterizing karate players will also be found.